If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 2y + 3z = 0 Solving x + 2y + 3z = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. x + 2y + -2y + 3z = 0 + -2y Combine like terms: 2y + -2y = 0 x + 0 + 3z = 0 + -2y x + 3z = 0 + -2y Remove the zero: x + 3z = -2y Add '-3z' to each side of the equation. x + 3z + -3z = -2y + -3z Combine like terms: 3z + -3z = 0 x + 0 = -2y + -3z x = -2y + -3z Simplifying x = -2y + -3z
| -4(x+8)=-32-4x | | 9y+3=5y+10 | | 11x+18=62 | | x+3+x-6=7-4 | | 2/3*7x-9/10 | | -3k-8+7=-21 | | 10y+6=5y+21 | | 1/3xd=1/10 | | x+9-19+x=64-x-1 | | 9=17+3x | | 100y+5=75y+25 | | 8(4-y)+10y=6y | | 19x+(-5)=-26+12x | | M=3m+10 | | 5x+10x+17x+4x=360 | | 16x^3-20x^2+12x-15= | | 4(2+2r)-2(-r+1)=6r+-2r | | M-8=3m+2 | | 21=6(5r-2) | | 3x+3-9=3+7-4 | | 2x+3(x-8)=9-5x | | 8x-25=6x-5 | | 100/15 | | -7x+23=-21-31x | | 36k^3=35 | | 2x+2+6x+1=5x-21 | | -0.7x+2.3=-2.1-3.1x | | -3x=-64+1 | | (5k^2-4k-1/5k^2-12k-7) | | 4y+12=-4(2y+5) | | 120x^2-116x-28= | | -x/5=75 |